Gut microbiome and metabolome in aneurysm rat with hypertension after ginsenoside Rb1 treatment - Zeng, Zhaobin; Wang, Haibin; Yi, Renhui; Lou, Jianyun; Wen, Shuting; Hu, Zheng (Frontiers in Pharmacology, 2023)
Hypertension is a prominent risk factor for aneurysms, with prolonged high blood pressure exacerbating aneurysm development and rupture. Ginsenoside, an active component derived from ginseng, is extensively used in traditional herbal medicine and is believed to possess antihypertensive properties. Research has indicated that gut microbiota is associated with the occurrence and progression of various diseases, ranging from obesity and inflammatory bowel disease to hypertension. Several studies have suggested that ginsenosides may influence the gut microbiota. However, the potential relationship between ginsenosides, gut microbiota, blood pressure, and intracranial aneurysm remains inadequately explored. In this study, using a rat model, a comparative analysis revealed the mitigating effects of ginsenosides on both blood pressure and intracranial arteries. Furthermore, 16S rRNA sequencing identified marker genera within the gut microbiota of those treated with ginsenoside Rb1, specifically including Clostridium, Roseburia, Ruminococcus, and Treponema, as well as metabolites such as behenic acid, N-Acetylserotonin, Prostaglandin F2a, and Vitamin D2, all of which have been implicated in blood pressure regulation. These results revealed valuable insights into the effects of ginsenosides on hypertension and atheroma development.